801. Patients with Clostridioides difficile Infection Following Dental Antibiotic Prescription. (31st December 2020) - Wilson, Geneva M; Evans, Charlesnika T; Fitzpatrick, Margaret A; Poggensee, Linda; Echevarria, Kelly; Suda, Katie J
Abstract: Background: Dentists prescribe few broad-spectrum antibiotics but are the primary prescriber of clindamycin in the U.S. Data is scarce on the association of dental antibiotic prescribing and Clostridioides difficile infection (CDI). Here we present results from a longitudinal cohort of patients with a CDI positive diagnostic test 30 days after receiving an antibiotic prescribed by a dentist. Methods: A cohort of patients with antibiotic prescriptions within 7 days of a dental visit were identified from 2015-2018. From this cohort, patients with positive C. difficile test 30 days after a dental antibiotic were included. Chart reviews obtained information about the dental visit, antibiotic prescribed, and CDI diagnosis. Descriptive statistics were used to describe characteristics of those with CDI following a dental antibiotic. Results: 212, 763 Veterans received an antibiotic from a dentist between 2015-2018. Of them, 87 patients had a positive CDI test within 30 days of receiving their dental antibiotic. Over half (57.4%) of these patients had surgical dental visits and 45.9% had an oral infection coded. Dentists documented reasons for prescription was treatment of a local infection (40%) and post procedure prophylaxis (24%). Amoxicillin (54.0%) and clindamycin (40.2%) were the most commonly prescribed antibiotics. 65.7% of the patients that received clindamycin from the dentist had a documented penicillin allergy. 58.6% of patients had a preexisting gastrointestinal condition and 44.8% were taking gastric acid reducer medication. Only 19.5% of the antibiotic prescriptions met ADA guidelines for appropriate antibiotics (presence of gingival manipulation and a cardiac condition). CDI cases were treated with metronidazole (55.2%), or vancomycin (37.9%); 5.7% had no apparent treatment through the VA. The average number of days between the dental visit and CDI diagnosis was 18.9. Conclusion: The occurrence of CDI was infrequent after a dental antibiotic. However, clindamycin was prescribed more frequently in this cohort than published literature on dentist prescribing. Approximately half had a gastrointestinal risk factor for CDI. More research is needed to determine the type of patient most at risk for CDI following a dental antibiotic. Disclosures: All Authors : No reported disclosures